2022
DOI: 10.1155/2022/4934343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parecoxib Sodium Preemptive Analgesia on the Recovery Period of General Anesthesia in Patients Undergoing Glioma Resection

Abstract: Objective. To investigate the effect of parecoxib sodium preemptive analgesia on postoperative complications and postoperative recovery of patients undergoing glioma resection. Methods. A total of 200 eligible patients with low-grade gliomas in the functional brain area scheduled for an awake craniotomy between January 2017 and December 2020 were reviewed. The subjects were divided into two groups: the study group (n = 100) given dexmedetomidine plus parecoxib sodium for pre-emptive analgesia 30 minutes preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Five studies assessed the e cacy of COXIBs for headache control in the intervention versus control groups [27,28,[30][31][32], and one study assessed two different pain regimens employing COXIBs, in both the intervention and control groups [29]. The speci c COXIBs used, dosing, frequency, timing, and routes of administration varied; parecoxib 40 mg IV was most frequently employed (n=264) [27,[29][30][31], followed by celecoxib (n=93) [32] and rofecoxib (n=14) [28]. Pain scores were reported as mean or median at different time points, from the immediate postoperative period (0 hours) up to 72 hours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies assessed the e cacy of COXIBs for headache control in the intervention versus control groups [27,28,[30][31][32], and one study assessed two different pain regimens employing COXIBs, in both the intervention and control groups [29]. The speci c COXIBs used, dosing, frequency, timing, and routes of administration varied; parecoxib 40 mg IV was most frequently employed (n=264) [27,[29][30][31], followed by celecoxib (n=93) [32] and rofecoxib (n=14) [28]. Pain scores were reported as mean or median at different time points, from the immediate postoperative period (0 hours) up to 72 hours.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded a total of 3190 articles. Following the removal of duplicates, 2988 articles were screened, with 6 studies meeting eligibility criteria (Figure 1): four RCT [27][28][29][30] and two retrospective cohort studies [31,32]. All studies were conducted in neurosurgical patients (n=738), between 2006-2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Here, the afferent center of injurious stimulus was reduced in all patients via the administration of butorphanol and a non-steroidal anti-in ammatory drug (parecoxib sodium). [27] The mechanism of action of erector spinae plane block has been proposed to involve the analgesic and antiin ammatory effects of systemic absorbed local anesthetics. [28] There was a reasonable doubt as to whether ITPB possessed similar anti-in ammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were given PENG at 30min after drug injection, followed by general anesthesia. Earlier research showed that oxycodone (1mg Kg − 1 ) and parecoxib (40mg) sodium as a single preoperative dose administered was no safety problems [15,[20][21][22]. All patients who received the DAA-THA were given general anesthesia by senior anesthesiologists and were performed by the senior doctors in the same group, the anesthesiologists and doctors with more than ten years of experience.…”
Section: Study Drug and Perioperative Protocolmentioning
confidence: 99%